Rotated dn-lattices in dimensions power of 3 - Ferrari, Agnaldo J. [UNESP]; Jorge, Grasiele C.; de Andrade, Antonio A. [UNESP] (iPeak Academy, 2021)
In this work, we present constructions of families of rotated Dn-lattices which may be good for signal transmission over both Gaussian and Rayleigh fading channels. The lattices are obtained as sublattices of a family of rotated Z ⊕ Ak2 lattices, where Ak2 is a direct sum of k =3r−1−1 copies of 2 the A2-lattice, using free Z-modules in Z[ζ3r + ζ−1 3r]..
Keywords: Cyclotomic fields; Lattices; Signal transmission